KEANEKARAGAMAN JENIS TEGAKAN HUTAN TEMBAWANG DI DESA SEHE LUSUR KECAMATAN KUALA BEHE KABUPATEN LANDAK - Septiawan, Safri; Lumangkun, Agustine; Dewantara, Iswan (JURNAL HUTAN LESTARI, 2017)
Tembawang is a form of management area conducted by Dayak tribe community in West Kalimantan. By the aspect of local wisdom, tembawang is a tribute, moral ethics of ancestral values, inheritance of ownership to its descendants, and as knowledge in understanding the types of trees which is used as a reference of ownership if the original tree die, as economic aspect, tembawang is a source of community nutrition but its utilization is limited to house hold consumption and the economic value is relatively smaller. The forming of tembawang is done after farmers have shifting cultivation, where before leaving their former land they planted various kinds of timbers, fruits, sap, and spices as medicinal plants. Information on the diversity of tembawang timber stands has not been widely known yet. The research aims to obtain information about the diversity of tembawang timber standing stock and the dominant tree species in the Village of Sehe Lusur Sub District of Kuala Behe District of Landak. The research was conducted in the Village of Sehe Lusur Sub District of Kuala Behe District of Landak for Â± 4 weeks, from August 2016 until done. Data collection in the field using mixed method of transect and line plots by census in three different tembawang namely Nanga Ngundul, Sungai Babi, and Nanga Ngasap. The research result shows that stands are found for all growth rates of 34 species. The most dominant number with the highest INP value of the seedling level is Kelampai (Elateriospermum tapos), the largest sapling is Durian (Durio zibethinus), stands whose in medium pole are Melaban (Vitex pinnata), and the stands classified as tree is Krikik.Keywords: Biodiversity, Desa Sehe Lusur, Forest, Stand, Tembawang.